Polyanionic phosphate material, preparation method thereof and lithium ion battery
By using titanium phosphate compounds as the phosphorus source, NASICON type polyanionic phosphate materials are prepared, which solves the problems of product puffing and hardening caused by ammonia generation in traditional methods, and improves the thermal stability and production efficiency of the material.
Patent Information
- Application Number
- CN202311256798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
Traditional NASICON type polyanionic phosphate materials are prone to produce ammonia with a irritating odor during the sintering process, causing the product to expand and harden, and at the same time, high requirements for instruments and equipment and process methods.
The polyanionic phosphate material is prepared by sintering treatment, which avoids the formation of ammonia and the volatility of phosphorus, and reduces the requirements for instruments and equipment and process methods.
It effectively avoids product puffing and hardening problems, improves the thermal stability and production efficiency of the material, and simplifies the process flow.
Smart Images

Figure CN119706774A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a polyanionic phosphate material, a preparation method thereof, and a lithium ion battery. Background Art
[0002] In recent years, with the rapid development of new energy technologies and the promotion of new energy vehicles, lithium-ion batteries have been widely used in 3C, new energy vehicles and power storage scenarios as a convenient high-energy storage device. Traditional lithium-ion batteries use flammable organic electrolytes, which pose great safety risks in practical applications. Recently, solid-state electrolytes (SSE) are considered to be the key to improving the safety and energy density of lithium-ion batteries. They can significantly reduce the use of organic electrolytes and can even replace organic electrolytes with solid electrolytes.
[0003] Among oxide solid electrolytes, NASICON polyanionic phosphate materials are stable to air and water, and their ionic conductivity can reach 10 -3 S / cm, and is one of the most market-oriented solid electrolyte materials. Currently, NASICON-type polyanionic phosphate materials are mainly prepared by solid phase method, sol-gel method, coprecipitation method, molten salt method, etc. Among them, the solid phase method is low-cost and the simplest, but it usually produces a large amount of ammonia with a pungent smell during preparation, which makes the product swell, and has high requirements for instruments, equipment and process methods. Summary of the invention
[0004] Based on this, it is necessary to provide a polyanionic phosphate material and a preparation method thereof and a lithium ion battery to avoid problems such as product expansion and high requirements for instruments, equipment and process methods.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a method for preparing a polyanionic phosphate material, comprising the following steps:
[0007] Providing a precursor powder, wherein the precursor powder comprises a lithium source, an aluminum source and a phosphorus-titanium compound, and the lithium source, the aluminum source and the phosphorus-titanium compound are uniformly dispersed;
[0008] The precursor powder is sintered to prepare a polyanionic phosphate material.
[0009] In one embodiment, the phosphorus-titanium compound includes one or more of titanium phosphate, titanium hydrogen phosphate and titanium pyrophosphate;
[0010] Optionally, the lithium source includes one or more of lithium hydroxide, lithium acetate, lithium carbonate, lithium nitrate, lithium dihydrogen phosphate, lithium oxalate, lithium fluoride and lithium chloride;
[0011] Optionally, the aluminum source includes one or more of aluminum oxide, aluminum hydroxide, aluminum phosphate and aluminum metaphosphate.
[0012] In one embodiment, the precursor powder further comprises one or more of a titanium source and a silicon source;
[0013] Optionally, the titanium source includes one or more of titanium dioxide, titanium tetrachloride, tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate, isooctyl titanate, titanium acetylacetonate and a titanate coupling agent;
[0014] Optionally, the silicon source includes one or more of silicon dioxide, trichlorosilane, silicon tetrachloride, dichlorosilane and silane;
[0015] Optionally, in the precursor powder, the molar ratio of lithium, aluminum, titanium, silicon and phosphorus satisfies (1-1.1)*(1+x+y+z):x:(2-x):y:(3-y), wherein 0 <x≤1,0≤y≤1,0≤z≤0.2。
[0016] In one embodiment, the precursor powder is prepared by a method comprising the following steps:
[0017] Preparing a raw material mixed solution containing each raw material substance in the precursor powder;
[0018] Drying the raw material mixed solution to remove the dispersion medium in the raw material mixed solution to prepare the precursor powder;
[0019] Optionally, the solid content of the raw material mixture is 3% to 80%;
[0020] Optionally, the dispersion medium includes one or more of water, ethanol and isopropanol;
[0021] Optionally, the raw material mixture further contains a retarding additive;
[0022] Optionally, the retarding additive comprises one or more of glucose and sucrose.
[0023] In one embodiment, before drying the raw material mixture, the following steps are also included:
[0024] The raw material mixed solution is subjected to ball milling treatment.
[0025] In one embodiment, the drying process is a spray drying process;
[0026] Optionally, the spray drying process is one or more of a centrifugal spray drying process, a pressure atomization drying process and an air flow spray drying process;
[0027] Optionally, the inlet temperature of the spray drying process is 100°C to 290°C;
[0028] Optionally, the outlet temperature of the spray drying process is 80°C to 160°C.
[0029] In one embodiment, the sintering temperature is 600°C to 1000°C;
[0030] Optionally, the heating rate of the sintering process is 1°C / min to 15°C / min;
[0031] Optionally, the sintering treatment time is 1 hour to 12 hours.
[0032] In a second aspect, the present invention provides a polyanionic phosphate material, which is prepared by the above-mentioned method for preparing the polyanionic phosphate material.
[0033] In one embodiment, the general formula of the polyanionic phosphate material is Li 1+x+y+z Al x Ti 2- x Si y P 3-y O 12+z / 2 , where 0 <x≤1,0≤y≤1,0≤z≤0.2。
[0034] In a third aspect, the present invention provides a lithium-ion battery comprising the polyanionic phosphate material described above.
[0035] The present invention has the following beneficial effects:
[0036] Compared with traditional phosphorus source materials such as diammonium phosphate and phosphoric acid, the present invention uses phosphorus-titanium compounds as the phosphorus source of polyanionic phosphate materials. During the high-temperature sintering process, it will not decompose to generate ammonia with a pungent odor. Its good thermal stability is also conducive to reducing the volatilization of phosphorus, thereby avoiding problems such as product expansion and hardening caused by gas volatilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a physical picture of the polyanionic phosphate material prepared in Example 1;
[0038] Figure 2 This is a physical picture of the polyanionic phosphate material prepared in Comparative Example 1;
[0039] Figure 3 The XRD pattern of the polyanionic phosphate material prepared in Example 1;
[0040] Figure 4 This is the XRD pattern of the polyanionic phosphate material prepared in Example 7. DETAILED DESCRIPTION
[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0042] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] In lithium-ion batteries, liquid organic electrolytes pose a great safety hazard due to their flammability, and at the same time limit the energy density of lithium-ion batteries. Using solid electrolytes to replace organic electrolytes is expected to develop safe, reliable, and high-energy-density all-solid-state lithium-ion batteries. Among various solid electrolytes, the molecular formula of lithium-based NASICON solid electrolytes is AM(PO4)3, which has a three-dimensional network skeleton structure [M2P3O 12 ] has a very stable structure and has the advantages of high ionic conductivity, high density, good environmental stability and mild synthesis conditions. It has broad development prospects and application potentials.
[0045] In NASICON type polyanionic phosphate materials, A is a monovalent transport cation, such as alkali metal ions such as Na, K, and Li; M can be a divalent cation (such as Zn 2+ Mg 2+ and Ni 2+etc.), trivalent cations (such as Cr 3+ 、Al 3+ Sc 3+ , Fe 3+ 、In 3+ and Y 3+ etc.), tetravalent cations (such as Ti 4+ 、Zr 4+ ,Ge 4+ , Hf 4+ and Sn 4+ etc.) or pentavalent cations (such as V 5+ , Nb 5+ and As 5+ etc.); 5+ It can also be replaced by other ions (such as Si 4+ 、V 5+ , Nb 5+ etc.) doping or substitution.
[0046] At present, the preparation methods of NASICON type polyanionic phosphate materials mainly include high temperature solid phase method, sol-gel method, coprecipitation method, molten salt method and hydrothermal method. Among them, the high temperature solid phase method is a preparation method in which the raw materials are crushed and ground, and then sintered and crystallized at high temperature, which has the advantages of easy availability of raw materials, simple operation, and convenience for large-scale production. Affected by factors such as uneven mixing of raw materials, high sintering temperature, and long sintering time, the products of high temperature solid phase synthesis method usually have shortcomings such as uneven particle size and impurities (such as AlPO4, TiO2, etc.). At the same time, the phosphorus source in the raw material is commonly used in materials such as ammonium dihydrogen phosphate (NH4H2PO4) and phosphoric acid (H3PO4). Ammonium dihydrogen phosphate will decompose and generate ammonia with a pungent taste during the sintering process. The volatilization of gaseous products easily causes expansion problems, and phosphoric acid, as a corrosive inorganic medium-strong acid, has high requirements for instruments and equipment and environment.
[0047] Based on this, the first aspect of the present invention provides a method for preparing a polyanionic phosphate material, which is used to overcome the problems that when diammonium dihydrogen phosphate or phosphoric acid is used as the phosphorus source, ammonia gas will be generated, causing the product to swell and harden, and high requirements for instruments, equipment and environment.
[0048] In some embodiments, the method for preparing the polyanionic phosphate material comprises the following steps:
[0049] Providing a precursor powder, wherein the precursor powder comprises a lithium source, an aluminum source and a phosphorus-titanium compound, and the lithium source, the aluminum source and the phosphorus-titanium compound are uniformly dispersed;
[0050] The precursor powder is sintered to prepare a polyanionic phosphate material.
[0051] Compared with traditional phosphorus source materials such as diammonium phosphate and phosphoric acid, the present invention uses phosphorus-titanium compounds as the phosphorus source of polyanionic phosphate materials. During the high-temperature sintering process, it will not decompose to generate ammonia with a pungent odor. Its good thermal stability is also conducive to reducing the volatilization of phosphorus, thereby avoiding problems such as product expansion and hardening caused by gas volatilization.
[0052] In addition, the preparation method does not require the use of organic salt reagents and medium-strong acid reagents, has a simple process, and is easy to achieve large-scale production.
[0053] Optionally, the titanium phosphorus compound includes one or more of titanium phosphate (Ti3(PO4)4), titanium hydrogen phosphate (Ti(HPO4)2) and titanium pyrophosphate (TiP2O7).
[0054] Titanium phosphate is a new type of inorganic polymer material with the advantages of being non-toxic, acid and alkali resistant, high temperature resistant, heat resistant, flame retardant and radiation resistant; titanium hydrogen phosphate has a layered structure and is an inorganic ion exchanger with a good exchange and adsorption effect on lithium ions; titanium pyrophosphate is a cation exchanger with good thermal and chemical stability. These three phosphorus-titanium compounds have good thermal stability, which can prevent the volatilization of phosphorus during high-temperature sintering. At the same time, they have good ion exchange effects, which makes it easy to achieve the diffusion and transmission of ions during the sintering process, which is conducive to controlling the purity and particle size of the product.
[0055] Optionally, the lithium source includes one or more of lithium hydroxide (LiOH), lithium acetate (CH3COOLi), lithium carbonate (Li2CO3), lithium nitrate (LiNO3), lithium dihydrogen phosphate (LiH2PO4), lithium oxalate (Li2C2O4), lithium fluoride (LiF) and lithium chloride (LiCl).
[0056] It can be understood that the above-mentioned compounds in the lithium source include anhydrous compounds without bound water, and hydrates containing bound water, for example, lithium hydroxide monohydrate (LiOH·H2O).
[0057] Further optionally, the lithium source is selected from one or more of lithium hydroxide (LiOH), lithium carbonate (Li2CO3) and lithium dihydrogen phosphate (LiH2PO4).
[0058] Optionally, the aluminum source includes one or more of aluminum oxide (Al2O3), hydrated aluminum oxide (AlOOH), aluminum hydroxide (Al(OH)3), aluminum phosphate (AlPO4) and aluminum metaphosphate (Al(PO3)3).
[0059] It is to be understood that the above-mentioned compounds in the aluminum source include anhydrous compounds not containing bound water, and hydrates containing bound water, for example, hydrated aluminum oxide (AlOOH).
[0060] Further optionally, the aluminum source is selected from one or more of aluminum oxide (Al2O3) and aluminum hydroxide (Al(OH)3).
[0061] In some embodiments, the precursor powder further comprises one or more of a titanium source and a silicon source;
[0062] The titanium element in the phosphorus-titanium compound is the main source of titanium element in the polyanionic phosphate material. The additional addition of titanium source to the precursor powder can adjust the stoichiometric ratio of titanium element to improve the ionic conductivity of the product. 4+ For P in PO4 tetrahedron 5+ Substitution or doping can be performed to further improve the ionic conductivity of the product.
[0063] Optionally, the titanium source includes one or more of titanium dioxide (TiO2), titanium tetrachloride (TiCl4), tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate, isooctyl titanate, titanium acetylacetonate and titanate coupling agent. Further optionally, the titanium source is titanium dioxide (TiO2).
[0064] Optionally, the silicon source includes one or more of silicon dioxide (SiO2), trichlorosilane (SiHCl3), dichlorosilane (SiH2Cl2), silicon tetrachloride (SiCl4) and silane (SiH4). Further optionally, the silicon source is silicon dioxide (SiO2).
[0065] Optionally, the main component of the polyanionic phosphate material is a Li2O-Al2O3-TiO2-P2O5-based solid electrolyte and its doped derivatives, the general formula of which is Li 1+x+y+z Al x Ti 2-x Si y P 3-y O 12+z / 2 , where 0 <x≤1,0≤y≤1,0≤z≤0.2。
[0066] In some specific examples, in the general formula of the polyanionic phosphate material, the value of x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, the value of y can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, and the value of z can be 0, 0.02, 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18 or 0.20, etc.
[0067] In some specific examples, the general formula of the polyanionic phosphate material can be Li 1.2 Al 0.2 Ti 1.8 P3O 12 , Li 1.3 Al 0.3 Ti 1.7 P3O 12 , Li 1.4 Al 0.4 Ti 1.6 P3O 12 , Li 1.5 Al 0.5 Ti 1.5 P3O 12 , Li 1.4 Al 0.3 Ti 1.7 Si 0.1 P 2.9 O 12 and Li 1.4 Al 0.3 Ti 1.7 P3O 12.05 wait.
[0068] Optionally, in the raw material mixture, the molar ratio of lithium, aluminum, titanium, silicon and phosphorus satisfies (1-1.1)*(1+x+y+z):x:(2-x):y:(3-y), wherein 0 <x≤1,0≤y≤1,0≤z≤0.2。
[0069] According to the general formula of the polyanionic phosphate material, the molar ratio of lithium in the precursor powder is in excess of 0-10%. This is because the sintering temperature of the high-temperature solid phase synthesis method is high, and the lithium in the lithium source is easily volatilized, resulting in a low stoichiometric ratio of lithium in the polyanionic phosphate material, thereby reducing the ionic conductivity of the product. Therefore, making the molar ratio of lithium in the precursor powder in excess of 0-10% can prevent the volatilization of lithium from affecting the ionic conductivity of the product.
[0070] In some specific examples, the molar amount of lithium element in the raw material mixture exceeds the stoichiometric ratio of lithium element in the polyanionic phosphate material by 0, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0071] In some embodiments, the precursor powder is prepared by a method comprising the following steps:
[0072] Preparing a raw material mixed solution containing each raw material substance in the precursor powder;
[0073] Drying the raw material mixed solution to remove the dispersion medium in the raw material mixed solution to prepare the precursor powder;
[0074] Optionally, the solid content of the raw material mixture is 3% to 80%. In some specific examples, the solid content of the raw material mixture is 3%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or 80%, etc.
[0075] By controlling the solid content of the raw material mixture at 3% to 80%, the viscosity of the raw material mixture can be adjusted to make it fluid and easy to dry. At the same time, the solid content can be increased as much as possible under the condition of appropriate viscosity to increase the production efficiency of the polyanionic phosphate material.
[0076] Optionally, the dispersion medium includes one or more of water, ethanol and isopropanol. Further optionally, the dispersion medium includes one or more of deionized water, anhydrous ethanol and anhydrous isopropanol.
[0077] Optionally, the raw material mixture further contains a retarding additive, which can prevent the product from hardening.
[0078] Optionally, the retarding additive comprises one or more of glucose and sucrose.
[0079] In some embodiments, before drying the raw material mixture, the following steps are further included:
[0080] The raw material mixed solution is subjected to ball milling treatment.
[0081] Ball milling the raw material mixture can improve the quality of the product and produce a polyanionic phosphate material with high dispersibility and good phase composition uniformity. During the ball milling process, the size of the solid particles in the raw material mixture gradually decreases, which is conducive to the dispersion and mixing of the solid particles, and can mechanically activate the raw materials to reduce the sintering temperature.
[0082] In some embodiments, the drying process is a spray drying process.
[0083] Through spray drying treatment, the raw materials can be fully mixed and evenly mixed, which makes it easy to achieve diffusion and transmission of ions during sintering, obtain pure phase materials, and achieve controllable particle size, thus overcoming the problems of uneven product particle size and impurities in traditional high-temperature solid-phase methods.
[0084] Optionally, the spray drying process is one or more of a centrifugal spray drying process, a pressure atomization drying process and an air flow spray drying process.
[0085] Optionally, the inlet temperature of the spray drying process is 100°C to 290°C. In some specific examples, the inlet temperature of the spray drying can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 180°C, 200°C, 240°C, 270°C or 290°C, etc.
[0086] Optionally, the outlet temperature of the spray drying process is 80°C to 160°C. In some specific examples, the outlet temperature of the spray drying process can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C or 160°C, etc.
[0087] Optionally, the heating rate of the sintering treatment is 1°C / min to 15°C / min. In some specific examples, the heating rate of the sintering treatment can be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 10°C / min, 12°C / min or 15°C / min, etc.
[0088] Optionally, the sintering temperature is 600°C to 1000°C. In some specific examples, the sintering temperature may be 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C or 1000°C, etc.
[0089] Optionally, the sintering treatment time is 1 h to 12 h. In some specific examples, the sintering treatment time can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc.
[0090] In a second aspect, the present invention provides a polyanionic phosphate material, which is prepared by the above-mentioned method for preparing the polyanionic phosphate material.
[0091] Optionally, the general formula of the polyanionic phosphate material is Li 1+x+y+z Al x Ti 2-x Si y P 3-y O 12+z / 2 , where 0 <x≤1,0≤y≤1,0≤z≤0.2。
[0092] In a third aspect, the present invention provides a lithium-ion battery comprising the polyanionic phosphate material described above.
[0093] Optionally, one or more of the electrolyte, positive electrode material and negative electrode material of the lithium-ion battery contains the polyanionic phosphate material.
[0094] The present invention is further described in detail below in conjunction with specific examples. The raw materials used in the following examples, unless otherwise specified, are commercially available products.
[0095] Example 1
[0096] Please refer to Table 1. In this embodiment, x=0.3, y=0, z=0, that is, the general formula of the polyanionic phosphate material is Li 1.3 Al 0.3 Ti 1.7 P3O 12 The lithium source is lithium carbonate, the aluminum source is aluminum oxide, the phosphorus-titanium compound is titanium pyrophosphate, the titanium source is titanium dioxide, no silicon source and retarding additive are added, and the dispersion medium is deionized water.
[0097] (1) Lithium carbonate, aluminum oxide, titanium pyrophosphate and titanium dioxide are weighed according to the general formula of the polyanionic phosphate material, and the molar amount of lithium element in the lithium carbonate is controlled not to be excessive; lithium carbonate, aluminum oxide, titanium pyrophosphate and titanium dioxide are added to deionized water, ball-milled, and prepared into a raw material mixed solution with a solid content of 49%.
[0098] (2) The raw material mixture is transported to a centrifugal spray dryer for drying, and the inlet temperature is set to 180° C. and the outlet temperature is set to 140° C. to obtain a precursor powder.
[0099] (3) The precursor powder is transferred to a sintering container, the temperature is increased to 900° C. at a heating rate of 1° C. / min, and sintered at 900° C. for 6 h to obtain a polyanionic phosphate material.
[0100] Example 2
[0101] Please refer to Table 1. In this embodiment, x=0.2, y=0, z=0, that is, the general formula of the polyanionic phosphate material is Li 1.2 Al 0.2 Ti 1.8 P3O 12 The lithium source is lithium hydroxide, the aluminum source is aluminum hydroxide, the phosphorus-titanium compound is titanium hydrogen phosphate, the titanium source is titanium dioxide, no silicon source and retarding additive are added, and the dispersion medium is anhydrous ethanol.
[0102] (1) Lithium hydroxide, aluminum hydroxide, titanium hydrogen phosphate and titanium dioxide are weighed according to the general formula of the polyanionic phosphate material, and the molar amount of lithium element in the lithium hydroxide is controlled not to be excessive; the lithium hydroxide, aluminum hydroxide, titanium hydrogen phosphate and titanium dioxide are added to anhydrous ethanol, and ball-milled to prepare a raw material mixed solution with a solid content of 3%.
[0103] (2) The raw material mixture is transported to a pressure spray dryer for drying, and the inlet temperature is set to 100° C. and the outlet temperature is set to 80° C. to obtain a precursor powder.
[0104] (3) The precursor powder is transferred to a sintering container, the temperature is increased to 600° C. at a heating rate of 5° C. / min, and sintered at 600° C. for 12 h to obtain a polyanionic phosphate material.
[0105] Example 3
[0106] Please refer to Table 1. In this embodiment, x=0.5, y=0, z=0, that is, the general formula of the polyanionic phosphate material is Li 1.5 Al 0.5 Ti 1.5 P3O 12 The lithium source is lithium carbonate, the aluminum source is aluminum hydroxide, the phosphorus-titanium compound is titanium hydrogen phosphate, the retarding additive is sucrose, no titanium source and silicon source are added, and the dispersion medium is deionized water.
[0107] (1) Lithium carbonate, aluminum hydroxide and titanium hydrogen phosphate are weighed according to the general formula of the polyanionic phosphate material, the molar amount of lithium element in the lithium carbonate is controlled not to be excessive, and the content of sucrose is 5%; lithium carbonate, aluminum hydroxide, titanium hydrogen phosphate and sucrose are added to deionized water, ball-milled, and prepared into a raw material mixed solution with a solid content of 30%.
[0108] (2) The raw material mixture is transported to a centrifugal spray dryer for drying, and the inlet temperature is set to 290° C. and the outlet temperature is set to 160° C. to obtain a precursor powder.
[0109] (3) The precursor powder is transferred to a sintering container, the temperature is increased to 1000° C. at a heating rate of 15° C. / min, and sintered at 1000° C. for 1 h to obtain a polyanionic phosphate material.
[0110] Example 4
[0111] Please refer to Table 1. In this embodiment, x=0.4, y=0, z=0, that is, the general formula of the polyanionic phosphate material is Li 1.4 Al 0.4 Ti 1.6 P3O 12 The lithium sources are lithium carbonate and lithium dihydrogen phosphate, the aluminum source is aluminum oxide, the phosphorus-titanium compound is titanium phosphate, no titanium source, silicon source and retarding additive are added, and the dispersion medium is isopropanol.
[0112] (1) Lithium carbonate, lithium dihydrogen phosphate, aluminum oxide and titanium phosphate are weighed according to the general formula of the polyanionic phosphate material, and the total molar amount of lithium element in the lithium carbonate and lithium dihydrogen phosphate is controlled not to be excessive; lithium carbonate, lithium dihydrogen phosphate, aluminum oxide and titanium phosphate are added to isopropanol, and ball milled to prepare a raw material mixed solution with a solid content of 80%.
[0113] (2) The raw material mixture is transported to a pressure spray dryer for drying, and the inlet temperature is set to 140° C. and the outlet temperature is set to 120° C. to obtain a precursor powder.
[0114] (3) The precursor powder is transferred to a sintering container, the temperature is increased to 800° C. at a heating rate of 2° C. / min, and sintered at 800° C. for 9 h to obtain a polyanionic phosphate material.
[0115] Example 5
[0116] Please refer to Table 1. In this embodiment, x=0.3, y=0.1, z=0, that is, the general formula of the polyanionic phosphate material is Li 1.4 Al 0.3 Ti 1.7 Si 0.1 P 2.9 O 12 The lithium source is lithium carbonate, the aluminum source is aluminum oxide, the phosphorus-titanium compound is titanium pyrophosphate, the titanium source is titanium dioxide, the silicon source is silicon dioxide, no retarding additive is added, and the dispersion medium is deionized water.
[0117] (1) Lithium carbonate, aluminum oxide, titanium pyrophosphate, titanium dioxide and silicon dioxide are weighed according to the general formula of the polyanionic phosphate material, and the molar amount of lithium element in the lithium carbonate is controlled not to be excessive; lithium carbonate, aluminum oxide, titanium pyrophosphate, titanium dioxide and silicon dioxide are added to deionized water, and ball-milled to prepare a raw material mixed solution with a solid content of 49%.
[0118] (2) The raw material mixture is transported to a centrifugal spray dryer for drying, and the inlet temperature is set to 140° C. and the outlet temperature is set to 120° C. to obtain a precursor powder.
[0119] (3) The precursor powder is transferred to a sintering container, the temperature is increased to 950° C. at a heating rate of 6° C. / min, and sintered at 950° C. for 9 h to obtain a polyanionic phosphate material.
[0120] Example 6
[0121] Please refer to Table 1. In this embodiment, x=0.3, y=0, z=0.1, that is, the general formula of the polyanionic phosphate material is Li 1.4 Al 0.3 Ti 1.7 P3O12.05 The lithium source is lithium carbonate, the aluminum source is aluminum oxide, the phosphorus-titanium compound is titanium pyrophosphate, the titanium source is titanium dioxide, no silicon source and retarding additive are added, and the dispersion medium is deionized water.
[0122] (1) Lithium carbonate, aluminum oxide, titanium pyrophosphate and titanium dioxide are weighed according to the general formula of the polyanionic phosphate material, and the molar amount of lithium element in the lithium carbonate is controlled to be 10% excess; lithium carbonate, aluminum oxide, titanium pyrophosphate and titanium dioxide are added to deionized water, ball-milled, and prepared into a raw material mixed solution with a solid content of 49%.
[0123] (2) The raw material mixture is transported to a pressure spray dryer for drying, and the inlet temperature is set to 140° C. and the outlet temperature is set to 120° C. to obtain a precursor powder.
[0124] (3) The precursor powder is transferred to a sintering container, the temperature is increased to 800° C. at a heating rate of 5° C. / min, and sintered at 800° C. for 9 h to obtain a polyanionic phosphate material.
[0125] Example 7
[0126] The difference between this comparative example and Example 1 is that spray drying is not used.
[0127] Please refer to Table 1. In this comparative example, x=0.3, y=0, z=0, that is, the general formula of the polyanionic phosphate material is Li 1.3 Al 0.3 Ti 1.7 P3O 12 The lithium source is lithium carbonate, the aluminum source is aluminum oxide, the phosphorus-titanium compound is titanium pyrophosphate, the titanium source is titanium dioxide, and no silicon source, retarding additive or dispersion medium is added.
[0128] (1) Lithium carbonate, aluminum oxide, ammonium dihydrogen phosphate and titanium dioxide are weighed according to the general formula of the polyanionic phosphate material, and the molar amount of lithium element in the lithium carbonate is controlled to be 10% excess; lithium carbonate, aluminum oxide, ammonium dihydrogen phosphate and titanium dioxide are mixed to obtain a precursor powder.
[0129] (2) The precursor powder is transferred to a sintering container, the temperature is increased to 900° C. at a heating rate of 1° C. / min, and sintered at 900° C. for 6 h to obtain a polyanionic phosphate material.
[0130] Comparative Example 1
[0131] The difference between this comparative example and Example 1 is that no phosphorus-titanium compound and spray drying are used.
[0132] Please refer to Table 1. In this comparative example, x=0.3, y=0, z=0, that is, the general formula of the polyanionic phosphate material is Li1.3 Al 0.3 Ti 1.7 P3O 12 The lithium source is lithium carbonate, the aluminum source is aluminum oxide, the phosphorus source is diammonium phosphate, the titanium source is titanium dioxide, and no silicon source, retarding additive or dispersion medium is added.
[0133] (1) Lithium carbonate, aluminum oxide, ammonium dihydrogen phosphate and titanium dioxide are weighed according to the general formula of the polyanionic phosphate material, and the molar amount of lithium element in the lithium carbonate is controlled to be 10% excess; lithium carbonate, aluminum oxide, ammonium dihydrogen phosphate and titanium dioxide are mixed to obtain a precursor powder.
[0134] (2) The precursor powder is transferred to a sintering container, the temperature is increased to 900° C. at a heating rate of 1° C. / min, and sintered at 900° C. for 6 h to obtain a polyanionic phosphate material.
[0135] Test Case
[0136] (1) Observe the appearance of the polyanionic phosphate material and record whether the product is expanded and hardened. The results are shown in Table 1. The actual image of the polyanionic phosphate material of Example 1 is shown in Table 1. Figure 1 As shown, the physical picture of the polyanionic phosphate material of Comparative Example 1 is as follows Figure 2 shown.
[0137] From Table 1 and Figures 1-2 It can be seen that the polyanionic phosphate materials of Examples 1 to 7 do not swell or harden, while the polyanionic phosphate material of Comparative Example 1 swells severely and hardens significantly. This shows that after replacing the traditional phosphorus source material diammonium phosphate with a phosphorus-titanium compound, no ammonia is generated during the high-temperature sintering process, and the volatilization of phosphorus is reduced, thereby avoiding the phenomenon of swelling and hardening of the product.
[0138] (2) Using a Rigaku MiniFlex600 X-ray diffractometer, the polyanionic phosphate materials of Examples 1 and 7 were subjected to XRD testing using CuKα radiation at a scanning speed of 10° / min. The results are as follows: Figures 3-4 shown.
[0139] Depend on Figure 3 It can be seen that the XRD pattern of the polyanionic phosphate material of Example 1 only shows the characteristic peak of NASICON structure (i.e., XRD standard card number PDF#35-0754), and no impurity phase peak appears; Figure 4It can be seen that the XRD pattern of the polyanionic phosphate material of Example 7 not only has the characteristic peaks of the NASICON structure, but also has obvious peaks of the raw materials and the intermediate product AlPO4 or TiP2O7 phase. This shows that spray drying is conducive to fully mixing the raw materials and facilitating the diffusion and transmission of ions during the sintering process, thereby obtaining a pure phase product.
[0140] Table 1. Parameters of polyanionic phosphate materials
[0141]
[0142]
[0143] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0144] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims, and the description and drawings can be used to interpret the content of the claims.
Claims
1. A method for preparing a polyanionic phosphate material, characterized in that: The following steps are involved: Providing a precursor powder, wherein the precursor powder comprises a lithium source, an aluminum source and a phosphorus-titanium compound, and the lithium source, the aluminum source and the phosphorus-titanium compound are uniformly dispersed; The precursor powder is sintered to prepare a polyanionic phosphate material.
2. The method for preparing the polyanionic phosphate material according to claim 1, characterized in that: The phosphorus-titanium compound includes one or more of titanium phosphate, titanium hydrogen phosphate and titanium pyrophosphate; Optionally, the lithium source includes one or more of lithium hydroxide, lithium acetate, lithium carbonate, lithium nitrate, lithium dihydrogen phosphate, lithium oxalate, lithium fluoride and lithium chloride; Optionally, the aluminum source includes one or more of aluminum oxide, aluminum hydroxide, aluminum phosphate and aluminum metaphosphate.
3. The method for preparing the polyanionic phosphate material according to claim 1, characterized in that: The precursor powder also includes one or more of a titanium source and a silicon source; Optionally, the titanium source includes one or more of titanium dioxide, titanium tetrachloride, tetramethyl titanate, tetraethyl titanate, tetrapropyl titanate, tetraisopropyl titanate, tetrabutyl titanate, isooctyl titanate, titanium acetylacetonate and a titanate coupling agent; Optionally, the silicon source includes one or more of silicon dioxide, trichlorosilane, silicon tetrachloride, dichlorosilane and silane; Optionally, in the precursor powder, the molar ratio of lithium, aluminum, titanium, silicon and phosphorus satisfies (1-1.1)*(1+x+y+z):x:(2-x):y:(3-y), wherein 0 <x≤1,0≤y≤1,0≤z≤0.2。 4. The method for preparing the polyanionic phosphate material according to any one of claims 1 to 3, characterized in that: The precursor powder is prepared by a method comprising the following steps: Preparing a raw material mixed solution containing each raw material substance in the precursor powder; Drying the raw material mixed solution to remove the dispersion medium in the raw material mixed solution to prepare the precursor powder; Optionally, the solid content of the raw material mixture is 3% to 80%; Optionally, the dispersion medium includes one or more of water, ethanol and isopropanol; Optionally, the raw material mixture further contains a retarding additive; Optionally, the retarding additive comprises one or more of glucose and sucrose.
5. The method for preparing the polyanionic phosphate material according to claim 4, characterized in that: Before drying the raw material mixed liquid, the method further comprises the following steps: The raw material mixed solution is subjected to ball milling treatment.
6. The method for preparing the polyanionic phosphate material according to claim 4, characterized in that: The drying process is spray drying process; Optionally, the spray drying process is one or more of a centrifugal spray drying process, a pressure atomization drying process and an air flow spray drying process; Optionally, the inlet temperature of the spray drying process is 100°C to 290°C; Optionally, the outlet temperature of the spray drying process is 80°C to 160°C.
7. The method for preparing the polyanionic phosphate material according to any one of claims 1 to 3 and 5 to 6, characterized in that: The sintering temperature is 600°C to 1000°C; Optionally, the heating rate of the sintering process is 1°C / min to 15°C / min; Optionally, the sintering treatment time is 1 hour to 12 hours.
8. A polyanionic phosphate material, characterized in that: The polyanionic phosphate material is prepared by the preparation method of the polyanionic phosphate material as described in any one of claims 1 to 7.
9. The polyanionic phosphate material according to claim 8, characterized in that The general formula of the polyanionic phosphate material is Li 1+x+y+z Al x Ti 2-x Si y P 3-y O 12+z / 2 , where 0 <x≤1,0≤y≤1,0≤z≤0.2。 10. A lithium ion battery, characterized in that: Contains the polyanionic phosphate material as claimed in claim 8 or 9.